Differentiating Peripherally-Located Small Cell Lung Cancer From Non-small Cell Lung Cancer Using a CT Radiomic Approach - Chen, Bihong T.; Chen, Zikuan; Ye, Ningrong; Mambetsariev, Isa; Fricke, Jeremy; Daniel, Ebenezer; Wang, George; Wong, Chi Wah; Rockne, Russell C.; Colen, Rivka R.; Nasser, Mohd W.; Batra, Surinder K.; et al. (Frontiers in Oncology, 2020)
Lung cancer can be classified into two main categories: small cell lung cancer (SCLC) and non-small cell lung cancer (NSCLC), which are different in treatment strategy and survival probability. The CT images of SCLC and NSCLC are similar such that their subtle differences are hardly visually discernible by the human eye through conventional imaging evaluation. We hypothesize that SCLC/NSCLC differentiation could be achieved via a computerized imaging feature analysis and classification. The purpose of this study was to use CT radiomics to differentiate SCLC from NSCLC adenocarcinoma. Patients with primary lung cancer, either SCLC or NSCLC adenocarcinoma, were retrospectively identified. The post-diagnosis pre-treatment lung CT images were used to segment the lung cancer. Radiomic features were extracted from histogram-based statistics and textural analysis of tumor images and their wavelet transforms. A minimal-redundancy-maximal-relevance method was used for feature selection. The predictive model was constructed with a multilayer artificial neural network. The performance of the SCLC/NSCLC adenocarcinoma classifier was evaluated by the area under the receiver operating characteristic curve (AUC). Our study cohort consisted of 69 primary lung cancer patients with SCLC (n=35; age mean ± SD = 66.91± 9.75 years), and NSCLC adenocarcinoma (n=34; age mean ± SD=58.55 ± 11.94 years). The SCLC group had more male patients and smokers than the NSCLC group (P<0.05). Our SCLC/NSCLC classifier achieved an overall performance of AUC of 0.93 (95% confidence interval = [0.85, 0.97]), sensitivity=0.85, and specificity=0.85). Adding clinical data such as smoking history improved the performance slightly. The top ranking radiomic features were mostly textural features. Our results showed that CT radiomics could quantitatively represent tumor heterogeneity and therefore could be used to differentiate primary lung cancer subtypes with satisfying results. CT image processing with the wavelet transformation technique enhanced the radiomic features for SCLC/NSCLC classification. Our pilot study should motivate further investigation of radiomics as a non-invasive approach for early diagnosis.